Penetapan Kadar Fenol Total dan Pengujian Aktivitas Antioksidan Minyak Jahe Gajah (Zingiber officinale var. officinale) (Determination of Total Phenolic Content and Antioxidant Activity of Jahe Gajah (Zingiber officinale var. officinale) Oil) - Tsabit Barki; Nia Kristiningrum; Endah Puspitasari; Fifteen Aprila Fajrin (Pustaka Kesehatan, 2017)
Jahe gajah (Zingiber officinale var. officinale) is one of export commodity plant in Indonesia. Part of jahe gajah often to be used is the rhizome, that content lots of essentials oil. One of the essential oil content is a phenolic compound. Phenolic compound is a natural product function as antioxidant reducing oxidative damage in the body that cause inflammation. The aim of this study was to determine the total phenolic content and antioxidant activity of jahe gajah oil. The total phenol content was determined using Folin-Ciocalteu method and the antioxidant activity assay was done using DPPH method. The total phenol content for jahe gajah oil was 0.626 ± 0.022 mg GAE/g . The IC50 of jahe gajah oil was 5,766 ± 0,087 µl/ml. Antioxidant activity from jahe gajah oil was suggested to be contributed by the phenolic compound and result from synergistic action of all constituents. Keywords: essential oil, aktivitas antioxidant, phenolic content